Application of the method of the optical flow analysis to control the parameters of passenger traffic - Сіроклин, Іван Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
The article denotes the actual problem of automatic control of parameters of passenger traffic to optimize the use of transport. It was suggested to apply the methods of automatic video image analysis for problems of control of parameters of subway passenger traffic. The article examines the application of the method of optical flow analysis. The model for studies was built with Simulink programme of MatLab software package. The standard model of the program was improved to reflect the conditions of underground, to reduce the influence of interferences, to interpret correctly the results, and to ease the visualization. As a result of the research the video fragments are classified according to the density of image filling by controlled objects. The error of the method for each of the classes was calculated. The results are presented as a graphical dependence. The scope of application of the suggested method of control of parameters of subway passenger traffic was determined